Influence of Quality of Work Life on Job Satisfaction among Educational Personnel in Semarang State Polytechnic - Rustono, Rustono -; BU, Rr Ririn; Sadriatwati, Sri Eka; Barokah, Siti Nur (Admisi dan Bisnis, 2019)
The objectives of this study are: 1). Analyzing Quality of Work Life (QWL) in Educational Personnel at Semarang State Polytechnic, 2). Analyzing the effect of Quality Of Work Life (QWL) factors on job satisfaction of Educational Personnel at Semarang State Polytechnic, 3). Analyzing which factors of Quality of Work Life (QWL) should be improved to achieve job satisfaction Education Personnel at Semarang State Polytechnic. Research conducted on 67 Education Personnel in Semarang State Polytechnic, the results of the analysis of the Effect of Quality of Work Life (QWL) consisting of Compensation, Career Development, Communication, Safe Environment, Occupational Health, Safety, Work on Conflict Resolution, Pride and Employee Participation on Job Satisfaction. Obtained the regression equation as follows: Y = 0.685 + 0.251X1 - 0.082X2 + 0.097X3 + 0.123X4 + 0.087X5 + 0.203X6-0.112X7 + 0.010X8 + 0.220X9. From the results of the study the variable Compensation, Safety, employee participation has a significant influence on the Job Satisfaction of Educational Personnel at the Semarang State Polytechnic The coefficient of determination (R2) obtained an adjusted R2 value of 0.61. This means that 61% of the variance in the Satisfaction of Educational Personnel at Semarang State Polytechnic. While the rest (100% - 61% = 39%) is explained by other factors outside the model.